2015
DOI: 10.1159/000436958
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-Enhanced Color Doppler Ultrasonography for Preoperative Evaluation of Sentinel Lymph Node in Breast Cancer Patients

Abstract: Background: Sentinel lymph node (SLN) biopsy is the standard of care for breast cancer patients with non-palpable axillary lymph nodes. We evaluated the usefulness of contrast-enhanced ultrasonography in preoperative detection of malignant SLNs. Methods: 50 patients with breast cancer (median age: 60 years) underwent a color power Doppler ultrasonography with intravenous contrast (Sonovue®) preoperatively, and findings suggestive of metastatic disease to the SLN were documented. The final histopathological rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 24 publications
2
22
0
Order By: Relevance
“…Sentinel lymph node biopsy is considered to be a standard method for axillary nodal assessment by most surgeons. Percutaneous SLN-CEUS is a suitable method for visualizing the SLN and the pathway of the LC in the SLNB procedure (Cox et al 2013;Dellaportas et al 2015;Sever et al 2012aSever et al , 2012b. Theoretically, the capillary lymphatic network forms a relatively dense mesh structure, called the areola lymphatic plexus, under the nipple areola (Gali e et al 2005;Sainte Marie et al 1982).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sentinel lymph node biopsy is considered to be a standard method for axillary nodal assessment by most surgeons. Percutaneous SLN-CEUS is a suitable method for visualizing the SLN and the pathway of the LC in the SLNB procedure (Cox et al 2013;Dellaportas et al 2015;Sever et al 2012aSever et al , 2012b. Theoretically, the capillary lymphatic network forms a relatively dense mesh structure, called the areola lymphatic plexus, under the nipple areola (Gali e et al 2005;Sainte Marie et al 1982).…”
Section: Discussionmentioning
confidence: 99%
“…However, this method cannot determine if the LN is the SLN, as well as the drainage of the LCs. Many studies have suggested that sentinel lymph node contrast-enhanced ultrasound (SLN-CEUS) can clearly define SLNs and LCs in breast cancer, with a sensitivity of 80.9%À100% and specificity of 70%À92.3% (Cox et al 2013;Dellaportas et al 2015;Sever et al 2012aSever et al , 2012b. Goldberg et al (2004) used intradermal injection in SLN-CEUS in a swine melanoma model to prove that microbubbles could successfully enter breast lymphatics and identify the axillary nodes.…”
Section: Introductionmentioning
confidence: 99%
“…Dellaportas et al reported their experience with CEUS using totally intravenous contrast injection for a preoperative detection of malignant SLN (93). They showed a negative predictive value of 90% and positive predictive value of 75%.…”
Section: Contrast Enhanced Ultrasound (Ceus) With Microbubblesmentioning
confidence: 99%
“…Although this possibility adds the risk of discomfort to the patient associated with a contrast injection, it carries the advantages of improved operative planning due to accurate knowledge of SLN locations and allows for more comprehensive preoperative patient counseling. Studies with other sonographic contrast agents describe the administration of contrast on the day prior to surgery . It is possible that perflubutane also has a longer duration of action, which would further increase the flexibility of the timing of the procedure and convenience for patients and facilities.…”
Section: Discussionmentioning
confidence: 99%
“…Studies with other sonographic contrast agents describe the administration of contrast on the day prior to surgery. 23 It is possible that perflubutane also has a longer duration of action, which would further increase the flexibility of the timing of the procedure and convenience for patients and facilities. More studies are needed to needed to clarify the exact duration of action of perflubutane to optimize clinical use.…”
Section: Discussionmentioning
confidence: 99%